The Influence of Principal's Managerial Competence and Infrastructure on Teacher Performance at Public Junior High Schools in Tapung District, Kampar Regency - Desi Awari; Mahdum Mahdum; Erlisnawati Erlisnawati (Journal of Educational Sciences, 2026)
This study examines the influence of principal managerial competence and school facilities on teacher performance in public junior high schools in Tapung District, Kampar Regency. Using a quantitative survey approach, data were collected from 157 teachers selected through random sampling and analyzed using multiple linear regression. The findings reveal that principal managerial competence has a positive and significant effect on teacher performance, with a regression coefficient of 0.122. School facilities also have a positive and more substantial influence, with a coefficient of 0.293, indicating that adequate infrastructure plays a greater role in supporting teacher effectiveness. Simultaneously, both variables contribute 24.7% to teacher performance, while 75.3% is affected by other factors beyond this study. These results highlight the importance of effective school leadership and adequate facilities in improving teacher performance. Therefore, teachers are encouraged to enhance professionalism through continuous development and instructional innovation. Principals should strengthen managerial practices and provide effective guidance for teachers, while schools must ensure the availability of supportive facilities. Additionally, the Education Office should implement policies, managerial training, and regular evaluations to improve school management quality and teacher competency sustainably.